2014
DOI: 10.1186/1757-2215-7-27
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of fucosylated haptoglobin alpha isoforms in ascitic fluids and its localization in ovarian carcinoma tissues from Mexican patients

Abstract: BackgroundOvarian cancer is the most lethal gynecologic disease due to delayed diagnosis, and ascites production is a characteristic of patients in advanced stages. The aim of this study was to perform the proteomic analysis of ascitic fluids of Mexican patients with ovarian carcinoma, in order to detect proteins with a differential expression pattern in the continuing search to identify biomarkers for this disease.MethodsSamples were collected from 50 patients from the Instituto Nacional de Cancerología of Mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“…Our previous studies have demonstrated the presence of a personalized signature of Hp α in the ascitic fluid of Mexican patients; moreover, we also showed that Hp is expressed in the cells from ovarian tumors at different stages. 19 Therefore, it was important to establish whether the cancer cell itself is capable of synthesising this protein to further understand its biological function within the tumoral environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have demonstrated the presence of a personalized signature of Hp α in the ascitic fluid of Mexican patients; moreover, we also showed that Hp is expressed in the cells from ovarian tumors at different stages. 19 Therefore, it was important to establish whether the cancer cell itself is capable of synthesising this protein to further understand its biological function within the tumoral environment.…”
Section: Resultsmentioning
confidence: 99%
“… 35 However, our group has demonstrated differences in both the expression level and the number of Hp α isoforms in ascitic fluid from patients who were diagnosed with different histological grades of ovarian carcinoma. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies on this antigen have shown that the overexpression of Lewis Y antigen promotes the human epididymis protein 4-mediated invasion and metastasis of ovarian cancer cells [15], p27 degradation by regulating ubiquitin-proteasome activity in the CAOV-3 and SKOV-3 cell lines [16], and chemotherapeutic resistance in ovarian cancer [17]. A few examples of modified fucosylated proteins are haptoglobin in several cancers, including ovarian cancer [18][19][20], transferrin and alpha-fetoprotein in liver cancer [21,22] and thyroglobulin in thyroid cancer [23]. In particular, previous results from our group have shown that the level of fucosylation of haptoglobin increases with stage progression [19] and was found to be highly fucosylated in different subtypes of epithelial ovarian cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…Another two fucosylated glycoproteins, kininogen and alpha-1-antitrypsin (a1AT), have been identified as candidates of hepatic tumor markers [7, 8]. In addition, it has been proven that core-fucosylated haptoglobin is a much better biomarker in ovarian carcinoma than simply monitoring the expression of the haptoglobin [9]. All the examples show that, during pathological processes, CF-glycoprotein changes occur not only in protein abundance but also in the occupancy of CF-glycosylation.…”
Section: Introductionmentioning
confidence: 99%